Low‐volume high‐intensity interval training for cardiometabolic health. (18th April 2021) - Sabag, Angelo; Little, Jonathan P.; Johnson, Nathan A.
Abstract: High‐intensity interval training (HIIT) is characterised by short bouts of high‐intensity submaximal exercise interspersed with rest periods. Low‐volume HIIT, typically involving less than 15 min of high‐intensity exercise per session, is being increasingly investigated in healthy and clinical populations due to its time‐efficient nature and purported health benefits. The findings from recent trials suggest that low‐volume HIIT can induce similar, and at times greater, improvements in cardiorespiratory fitness, glucose control, blood pressure, and cardiac function when compared to more traditional forms of aerobic exercise training including high‐volume HIIT and moderate intensity continuous training, despite requiring less time commitment and lower energy expenditure. Although further studies are required to elucidate the precise mechanisms of action, metabolic improvements appear to be driven, in part, by enhanced mitochondrial function and insulin sensitivity, whereas certain cardiovascular improvements are linked to increased left ventricular function as well as greater central and peripheral arterial compliance. Beyond the purported health benefits, low‐volume HIIT appears to be safe and well‐tolerated in adults, with high rates of reported exercise adherence and low adverse effects. Abstract : Abstract figure legend Low‐volume high‐intensity interval training (HIIT) is safe and effective for improving cardiorespiratory fitness, cardiac function, blood glucose levels, and blood pressure. Typical low‐volume HIIT protocols involve one four‐minute interval or ten one‐minute intervals at intensities between 80‐100% of maximal oxygen uptake.